Molecular weight determination of adeno‐associate virus serotype 8 virus‐like particle either carrying or lacking genome via native nES gas‐phase electrophoretic molecular mobility analysis and nESI QRTOF mass spectrometry. (4th October 2021) - Zoratto, Samuele; Weiss, Victor U.; van der Horst, Jerre; Commandeur, Jan; Buengener, Carsten; Foettinger‐Vacha, Alexandra; Pletzenauer, Robert; Graninger, Michael; Allmaier, Guenter
Abstract: Virus‐like particles (VLPs) are proteinaceous shells derived from viruses lacking any viral genomic material. Adeno‐associated virus (AAV) is a non‐enveloped icosahedral virus used as VLP delivery system in gene therapy (GT). Its success as vehicle for GT is due to its selective tropism, high level of transduction, and low immunogenicity. In this study, two preparations of AAV serotype 8 (AAV8) VLPs either carrying or lacking completely genomic cargo (i.e., non‐viral ssDNA) have been investigated by means of a native nano‐electrospray gas‐phase electrophoretic mobility molecular analyzer (GEMMA) (native nES GEMMA) and native nano‐electrospray ionization quadrupole reflectron time‐of‐flight mass spectrometry (MS) (native nESI QRTOF MS). nES GEMMA is based on electrophoretic mobility principles: single‐charge nanoparticles (NPs), that is, AAV8 particle, are separated in a laminar sheath flow of dry, particle‐free air and a tunable orthogonal electric field. Thus, the electrophoretic mobility diameter (EMD) of a bio‐NP (i.e., diameter of globular nano‐objects) is obtained at atmospheric pressure, which can be converted into its MW based on a correlation. First is the native nESI QRTOF. MS's goal is to keep the native biological conformation of an analyte during the passage into the vacuum. Subsequently, highly accurate MW values are obtained from multiple‐charged species after deconvolution. However, once applied to the analysis of megadalton species, native MS is challenging and requires customized instrumental modifications not readily available on standard devices. Hence, the analysis of AAV8 VLPs via native MS in our hands did not produce a defined charge state assignment, that is, charge deconvolution for exact MW determination was not possible. Nonetheless, the method we present is capable to estimate the MW of VLPs by combining the results from native nES GEMMA and native ESI QRTOF MS. In detail, our findings show a MW of 3.7 and 5.0 MDa for AAV8 VLPs either lacking or carrying an engineered genome, respectively.